Pengaruh Anggaran Pendidikan, Anggaran Kesehatan, dan Penerimaan Pajak Daerah terhadap Indeks Pembangunan Manusia pada Kabupaten/Kota di Jawa Timur Tahun 2015–2024 - Amirah Amjad Pranoto (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study analyzes the effect of education budget, health budget, and local tax revenue on the Human Development Index (HDI) in regencies/cities of East Java Province during 2015–2024. HDI is a key indicator of human development success, yet disparities across regions in East Java remain wide despite rising budget realization, raising questions about the effectiveness of local fiscal policy. The study draws on Human Capital Theory, Capability Theory, and Public Finance Theory as the theoretical foundation linking public spending, fiscal capacity, and human development. A quantitative approach was used with panel data of 380 observations (38 regencies/cities × 10 years), estimated with a Fixed Effect Model panel regression in Eviews 12, following the Chow and Hausman tests. Results show that the education budget has a negative and significant effect on HDI, while health budget and local tax revenue each have a positive and significant effect. Simultaneously, all three variables significantly affect HDI, with an Adjusted R-squared of 93.52 percent. These findings indicate that HDI improvement depends not merely on budget size but also on the effectiveness and governance of local fiscal management, suggesting local governments re-evaluate education budget allocation while strengthening fiscal capacity through optimized local tax revenue collection.